Epigeic invertebrate fauna associated with different systems of growing of coffee tree - Guimarães, Nathalia de França; Fontanetti, Anastácia; Fujihara, Ricardo Toshio; Gallo, Anderson de Souza; de Souza, Maicon Douglas Bispo; Morinigo, Kátia Priscilla Gomes; da Silva, Rogério Ferreira (Coffee Science - ISSN 1984-3909, 2017)
The study aimed to assess the structure community of the epigeic invertebrate fauna associated with different coffee tree farming systems. The experimental design was completely block in split plot in time, with five repetitions. Two seasons were evaluated, the first in April and the second in month July. The treatments consisted of three coffee tree cultivation systems and two witnesses areas: 1) Coffee tree intercropped with tree and Brachiaria decumbens species; 2) Coffee intercropped with B. decumbens; 3) Coffee in exclusive culture; 4) area with ground fallow and 5) native vegetation fragment. In each system were installed fivepitfall traps "pitfall" to capture epigeic invertebrate fauna. In addition, they evaluated the burlap accumulation (t ha-1) and soil moisture (kg kg-1), near the traps. The systems adopted favoured the groups Collembola, Diptera, Formicidae and mainly in times with greater precipitation. Coffee tree intercropped with B. decumbens and native vegetation fragment were more complex, with respect to community structure of soil fauna, followed by ground fallow, Coffee intercropped with B. decumbens and Coffee in exclusive culture.